Herbal medicine use and predictors among pregnant women attending antenatal care in Ethiopia: a systematic review and meta-analysis - Fentahun Adane; Girma Seyoum; Yoseph Merkeb Alamneh; Worku Abie; Melaku Desta; Bihonegn Sisay (BMC, 2020)
Abstract Background The use of herbal medicine among pregnant women is increasing in many low- and high-income countries due to their cost-effectiveness in treatment and ease of access. Research findings across Ethiopia on the prevalence and predictors of herbal medicine use among pregnant women attending antenatal care are highly variable and inconsistent. Therefore, this systematic review and meta-analysis aims to estimate the overall prevalence of the use of herbal medicine and its predictors among pregnant women attending antenatal care in Ethiopia. Method We searched articles in Medline (PubMed), EMBASE, HINARI, Google Scholar, Science Direct, Cochrane Library, and other sources. The study included a total of eight studies that reported the prevalence and predictors of herbal medicine use among pregnant women from different regions of Ethiopia. Cochrane Q test statistics and I2 tests were used to assess heterogeneity. A random effect meta-analysis model was used to estimate the pooled prevalence. In addition, the association between risk factors and herbal medicine use in pregnant women attending antenatal care were examined. Results A total of eight studies were included in this review. The pooled prevalence of herbal medicine use among pregnant women attending antenatal care in Ethiopia was 47.77% (95% CI: 28.00-67.55). Subgroup analysis by geographic regions has showed that the highest prevalence (57.49%;95% CI: 53.14, 61.85) was observed in Oromia Region and the lowest prevalence was observed in Addis Ababa (31.39%; 95% CI: 2.83, 79.96). The herbal medicines commonly consumed by women during pregnancy were ginger: 41.11% (95% CI: 25.90, 56.32), damakasse: 34.63% (95% CI: 17.68, 51.58), garlic: 32.98% (95% CI: 22.21, 43.76), tenaadam: 19.59% (95% CI: 7.54, 31.63) and eucalyptus: 4.71% (95% CI: 1.1, 8.26). Mothers' previous history of self-medication (95% CI: 1.91, 51.35), illness during pregnancy (95% CI: 1.56, 23.91), employment status (95% CI: 3.89, 10.89), educational status (95% CI: 1.52, 2.68), and place of residence (95% CI: 1.86, 3.23) were predictors of herbal medicine use by women during pregnancy. Conclusion In this study, about half of women attending antenatal care use herbal medicine and it is relatively high. The most commonly consumed herbal medicine during pregnancy was ginger followed by damakasse, garlic, tenaadam and eucalyptus. During pregnancy, it is not known that these most commonly consumed plant species have harmful fetal effects. However, many of the medicinal plant species are poorly studied, and it is not possible to rule out teratogenic effects. Teamwork between healthcare professionals and traditional practitioners to educate on the use of medicinal plants will encourage healthier pregnancies and better health for mothers and infants.